RETRACTED: Yizhi Qingxin Formula Extract Ameliorates Cognitive Decline in Aged Rats via the Brain-Derived Neurotrophic Factor/Tropomyosin Receptor Kinase B Pathway - Ma, Lina; Cao, Yu; Wang, Feixue; Li, Zehui; Wang, Zhiyong; Yang, Yang; Pei, Hui; Li, Hao (Frontiers in Pharmacology, 2020)
Cognitive impairment and decline in old age are primarily driven by the accumulation of age-related neuropathologies, and old age is thus the primary risk factor for neurodegenerative diseases such as AD. Here, we investigated the effects of Yizhi Qingxin formula (YQF) extract on cognitive impairment in aged rats and determine the role of the brain-derived neurotrophic factor (BDNF)/ tropomyosin receptor kinase B (TrkB) pathway underlying the neuroprotective effects of the YQF extract. Fifty male Wistar rats were randomly divided into five groups: Control group, Model group, Donepezil group, and YQF extract groups (treatment with YQF extract at two different doses). After treatment with YQF extract for 8 weeks, learning and cognitive abilities were assessed using the Morris water maze. Morphological changes in the hippocampus were observed using hematoxylin-eosin and Nissl staining. Activated microglia and astrocytes were assessed using immunohistochemistry. Expressions of proteins and genes were examined using western blotting and real-time PCR. The results revealed that oral treatment with YQF extract dramatically improved spatial learning and memory ability and ameliorated histopathological and morphological characteristics in aged rats. YQF extract significantly increased acetylcholine and interleukin (IL)-10 levels but markedly decreased amyloid-β peptide, tumor necrosis factor alpha (TNFα), IL-2, and IL-6 levels. In addition, it inhibited the excessive activation of microglia and astrocytes, downregulated the expressions of TNFα and IL-2, and upregulated nerve growth factor, BDNF, and TrkB expressions. Furthermore, hippocampal extracellular signal-related kinase (Erk) and protein kinase B (Akt), the upstream signaling of BDNF/TrkB, were also activated by treatment with YQF extract. Our findings indicate that YQF extract activates the BDNF/TrkB pathway through the upregulation of Erk and Akt signaling, and the activated signaling pathway might contribute to the protective effects of YQF extract on cognitive impairment in aged rats.